Bypassing of primary healthcare for emergency departments in Saudi Arabia: A systematic review - Muminat O. Ahmad (Journal of Healthcare Administration)
Background: Bypassing primary healthcare (PHC) services for emergency departments (EDs) is a critical issue in healthcare management, significantly impacting healthcare delivery and resource allocation.